Springboard internationalization by emerging market firms: Speed of first cross-border acquisition - Kumar, Vikas; Singh, Deeksha; Purkayastha, Anish; Popli, Manish; Gaur, Ajai (Journal of International Business Studies, 2020)
According to the springboard perspective, emerging market multinationals seek strategic assets aggressively from the outset. In this paper, we investigate the role of firms’ institutional embeddedness in terms of age and affiliation to business group on their aggressive internationalization pursuits, an issue which has remained less explored in international business scholarship. This study, based on 8163 Indian listed firms over 18 years, identifies a trend that younger firms founded in the liberalized era, post 1991, and unaffiliated firms are more likely to pursue aggressive internationalization by conducting their first cross-border acquisition (CBA) faster. Among affiliated firms, younger ones are relatively faster in conducting their first CBA. Furthermore, the evidence signals a moderating impact of inter-group heterogeneity in terms of group-level assets and foreign investments on the relationship between firm age and aggressive internationalization.